Hierarchical N-doped carbon spheres anchored with cobalt nanocrystals and single atoms for oxygen reduction reaction. (September 2021) - Shi, Changwei; Liu, Yuheng; Qi, Ruiyu; Li, Jiantao; Zhu, Jiexin; Yu, Ruohan; Li, Shidong; Hong, Xufeng; Wu, Jinsong; Xi, Shibo; Zhou, Liang; Mai, Liqiang
Abstract: Carbon-supported transition metal catalysts have attracted intense interest for oxygen reduction reaction (ORR) due to their high activity and low cost. Herein, we report bimetallic zeolitic imidazole frameworks (BMZIF)-derived hierarchical N-doped carbon spheres anchored with graphene-encapsulated Co nanocrystals (Co@C) and spatially isolated single Co atoms (Co SAs) (denoted as Co-NCS) for highly efficient ORR. An ultrasonic strategy has been developed to uniformly anchor BMZIF on resin microspheres. The ultrasonic method significantly shortens the synthesis time and contributes to the homogeneous distribution of BMZIF. The inner resin spheres act as ideal support to anchor Zn/Co ions and prevent the aggregation of BMZIF nanocrystals, and the derived products provide adequate structural support and high conductivity after carbonization. Meanwhile, the outer BMZIF-derived porous carbon framework provides large specific surface area, promoted electron transport, and abundant exposed active sites. The co-existence of Co SAs and Co@C plays a vital role in the ORR process. The resultant catalyst demonstrates superior ORR performance with a half-wave potential (J1/2 ) of 0.90 V, outperforming the commercial Pt/C. This work opens a new path to construct efficient Co-N-C based catalysts. Graphical Abstract: ga1 Highlights: A fast ultrasonic method was developed to uniformly anchor BMZIF on resin spheres. Resin spheres provide support for BMZIF, prevent aggregation, improve conductivity. BMZIF-derived carbon framework increases transport pathways, exposes active sites. Co-existence of Co single atoms and Co nanocrystals plays vital role in the ORR.